Work-Life Balance and Performance of Female Medical Practitioners of Federal Government owned Medical Centres in Edo State, Nigeria - A, Akhator, P.; Itua, Ohue Paul (Journal of Accounting, Business and Finance Research, 2019)
The broad objective of this paper is to determine the effect of work-life balance on performance of female medical practitioners of federal government owned medical centres in Edo state. Specifically, this study seeks to ascertain the effect of employee support on the commitment of married female medical practitioners of university of Benin teaching hospital and Irrua specialist teaching hospital. Survey research design was adopted for the study, a sample size of two hundred and eighty (280) was used for the study, Krejcie and Morgan, (1970) sampling technique was used for the study, the data collection tool employed by the researchers was the questionnaire, while the analysis of the data was done using the linear regression analysis. The findings revealed that employee support impacts the commitment of married female medical practitioners of university of Benin teaching hospital and Irrua specialist teaching hospital, Edo state since (F = 964.986; R2 = 0.836; P <.05). The researchers therefore concluded that work-life balance impacts employee performance of the institutions in focus. Based on the foregoing, the researchers recommended the enactment of favourable work-life balance policies by the institutions in focus and the approval of emergency leave for female (married) medical practitioners of the institutions in focus because of their role in the family.